Gene Expression Profiling of PDGFRA Mutant GIST Reveals Immune Signatures as a Specific Fingerprint of D842V Exon 18 Mutation - Indio, Valentina; Ravegnini, Gloria; Astolfi, Annalisa; Urbini, Milena; Saponara, Maristella; De Leo, Antonio; Gruppioni, Elisa; Tarantino, Giuseppe; Angelini, Sabrina; Pession, Andrea; Pantaleo, Maria Abbondanza; Nannini, Margherita (Frontiers in Immunology, 2020)
PDGFRA mutations occur in in only about 5–7 % of gastrointestinal stromal tumors (GIST), notably with alterations on exon 12/14/18. The most frequent PDGFRA mutation is the exon 18 D842V, which is correlated to specific clinical-pathological features as the primary imatinib resistance and the higher indolence. Here, we present a gene expression profile (GEP) comparison of D842V versus PDGFRA mutant other than D842V (non-D842V). GEP was followed by in silico bioinformatic analysis aimed to evaluate differential expression, tumor microenvironment composition and pathway enrichment. We found a large set of oncogenes, transcription factors and nuclear receptors downregulated in D842V mutant. Conversely, D842V showed significant enrichment of immune- and interferon- related gene signatures. Differences in tumor microenvironment composition were also highlighted, including a higher abundance of CD8+ T-cells and an overexpression of the T cell-inflamed signature in D842V mutant subgroup, that is predictive of immunotherapy response. PDGFRA D842V versus non-D842V GIST display a different expression profile, with a prominent immunological signature, that could represent a proof of principle for testing immunotherapeutic strategies in this drug-orphan subset of GIST.